Use of hybrid membrance system for the production of process water from biologically treated Palm Oil Mill Effluent (POME) - Idris, Munirat Abolore (Kulliyyah of Engineering, International Islamic University Malaysia, 2010)
The rapid and consistent growth in industrialization, infrastructures, and urban-expansions has led to increase in water demand and has also led to water pollution and deterioration. Agro-based industries are major organic pollutants of water bodies and the palm oil mill industry in Malaysia is one of the industries that produce the largest organic pollution load into the rivers. Palm Oil Mill Effluent (POME) is a highly voluminous liquid waste which is non toxic, have an unpleasant smell and very polluting. There is an urgent need to find a compromising way that will enable the balance between the environmental protection and sustainable reuse of the water in POME. Membrane technology especially ultrafiltration has become a recognized separation method that is well suited for the recycling and reuse of wastewater. Major drawbacks of using membrane includes fouling, and decline in permeate flux but the introduction of pretreatment units for modifications of feed water by removing suspended solids that may bring about pore clogging leading to membrane fouling is an effective way of improving the performance of membrane filtration system. This study aims at reclaiming water from biologically treated POME using hybrid membrane system consisting of pretreatment stages. Pretreatment stages of coagulation using ferric chloride and alum and adsorption using granular activated carbon (GAC) was one of the focal area ot this study. The effects of coagulant dose, pH and coagulant aid dose were investigated for the coagulation process and effect of bed height (mass of adsorbent) was carried out for the adsorption process. Also, the effect of transmembrane pressure, feed pretreatment and Molecular Weight Cut-Off (MWCO) on permeate flux and quality were investigated for the ultrafiltration membrane system. The result of the coagulation process showed that ferric chloride gave a better reduction of turbidity at dosage of 100mg/L, pH of 8 and with polyacrylamide (coagulant aid) dose of 100mg/L than alum. In the adsorption pretreatment process, Freundlich Isotherm was well fitted with the experimental data obtaining R2= 0.9862 than Langmuir isotherm of R2= 0.8646. Also, GAC with bed height of 0.4m gave better reductions of pollutant from the effluent with empty bed contact time (EBCT) of 21 minutes and carbon usage rate (CUR) of 2.27g/L. The results of the membrane filtration system showed that MWCO of 1 kDa gave the best permeate quality at 0.5 bar. The percentage reduction efficiency achieved by this hybrid system was 96% COD, 99.9% Turbidity, 99.9% Colour and 80% TDS. The quality of the effluent from this hybrid system was compared with the national standard for drinking water quality and the result shows that water can be reclaimed from biologically treated POME which can be reused in the oil mill as process water.